The Role of Informatics Teaching in Developing Critical Thinking and Computational Skills in High Schools - Wardani, Febri Pramudya; Sisca Widiyastuti; Hadassah Grace Ferisca; Tamariska Agape Scaferi; Lovely Olive Fesca (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study summarizes studies on the effects of informatics instruction on students' critical thinking and computational skills. The study used a mixed-method approach, combining qualitative analysis of teacher interviews, student surveys, and case studies of successful schools, as well as quantitative analysis of student learning outcomes. Findings indicate that the integration of project-based learning, problem-solving, and computational thinking into informatics curricula positively impacts students' critical thinking and computational skills. The study also identified key challenges in informatics instruction, such as resource constraints and the need for more in-depth teacher training. Recommendations are provided for the development of curricula, teaching strategies, and educational policies to support the effectiveness of informatics instruction